The Impact of Music Activities in a Multi-Sensory Room for Children with Multiple Disabilities on Developing Positive Emotions: a Case Study - Liza Lee; Tz Yuan Li (European Teacher Education Network, 2016)
The idea of a multi-sensory environment (MSE) is not only to provide stimulation for users with disabilities, but also to be calming. Through many studies by the research team, the results had proven the effectiveness of using music activities in multisensory environments for children with various types of disabilities. The purpose of the study was to duplicate the use of the multisensory environment teaching approach with music activities on developing positive emotions and other areas of development for a child with multiple disabilities. A 3 year-old boy with multiple disabilities was selected by purposive sampling to participate in the study. This was a 12-week study, with 50-minute sessions once per week in a group setting. Prior to the formal teaching, 4 observations were taken to determine the participant's current condition. Both qualitative and quantitative methods were used to assess the results. The results showed the positive impact of using music activities on increasing positive emotions for the participant in the multisensory environment. Furthermore, the finding for the participant's communication skills, social interaction with peers and level of intelligence were improved when the research sessions were assessed.